Monitoring techniques for the manufacture of tapered optical fibers - Mullaney, Kevin; Correia, Ricardo; Staines, Stephen E.; James, Stephen W.; Tatam, Ralph P. (OSA Publishing, 2015)
The use of a range of optical techniques to monitor the process of fabricating optical fiber tapers is investigated. Thermal imaging was used to optimize the alignment of the optical system; the transmission spectrum of the fiber was monitored to confirm that the tapers had the required optical properties and the strain induced in the fiber during tapering was monitored using in-line optical fiber Bragg gratings. Tapers were fabricated with diameters down to 5 μm and with waist lengths of 20 mm using single-mode SMF-28 fiber.